QUANTUM BROWNIAN PARTICLE AND MEMORY EFFECTS - BRINATI, JR; Mizrahi, S. S.; Pimentel, B. M. (American Physical Soc, 1991)
The quantum Brownian particle, immersed in a heat bath, is described by a statistical operator whose evolution is ruled by a generalized master equation (GME). The heat bath's degrees of freedom are considered to be either white-noise or colored-noise correlated, while the GME is considered under either the Markov or non-Markov approaches. The comparisons between these considerations are fully developed, and their physical meaning is discussed.